Management of midline diastema using pressable ceramics and zirconia crowns: a case series - Rayavarapu, Sunil; Yelisetty, Kalyan; Budumuru, Anil; Varma, N V Teja; Yekula, Prem Sagar (International Journal of Dental Materials, 2023)
Maxillary and mandibular midline diastema (MMD) is frequently observed in various populations. The occurrence of MMD can be attributed to multiple factors, including etiological, developmental, and patient habits. The diverse options to treat MMD are orthodontic correction, direct and indirect restorations, crowns, and veneers. This case series presents instances of closing maxillary and mandibular midline diastema using e.max veneers and zirconia crowns.